2013
DOI: 10.1182/blood-2012-10-460527
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 is required for chromosomal translocations

Abstract: • Chromosomal translocations are mediated by PARP1 and can be suppressed by the clinical PARP1 inhibitors.Chromosomal translocations are common contributors to malignancy, yet little is known about the precise molecular mechanisms by which they are generated. Sequencing translocation junctions in acute leukemias revealed that the translocations were likely mediated by a DNA double-strand break repair pathway termed nonhomologous endjoining (NHEJ). There are major 2 types of NHEJ: (1) the classical pathway init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 26 publications
2
79
0
Order By: Relevance
“…Concomitantly to the finding that PARP inhibitors increase the sensitivity of DNA-PK-deficient cells to radiomimetic-induced DSBs [45], biochemical experiments [45,48,49] and plasmid assays in Kudeficient cells [61] substantiated the involvement of PARP1 in a non [62,71,82,95,100,116,118,[149][150][151][152]154,160,161,163,168,169,171,174,180,182,184,185,264,[305][306][307] Translocation IR, etoposide, Zn-finger nucleases [94,240,245,303,308] RAG, AID, spontaneous [62,95,100,152,154,162,163,171,240,261,269,…”
Section: End Recognition and Tethering Of Dsb Endsmentioning
confidence: 84%
“…Concomitantly to the finding that PARP inhibitors increase the sensitivity of DNA-PK-deficient cells to radiomimetic-induced DSBs [45], biochemical experiments [45,48,49] and plasmid assays in Kudeficient cells [61] substantiated the involvement of PARP1 in a non [62,71,82,95,100,116,118,[149][150][151][152]154,160,161,163,168,169,171,174,180,182,184,185,264,[305][306][307] Translocation IR, etoposide, Zn-finger nucleases [94,240,245,303,308] RAG, AID, spontaneous [62,95,100,152,154,162,163,171,240,261,269,…”
Section: End Recognition and Tethering Of Dsb Endsmentioning
confidence: 84%
“…B-NHEJ causes more extensive deletions at DSB junctions than D-NHEJ and, importantly, markedly promotes chromosome translocations (15)(16)(17). Thus, B-NHEJ is now widely considered as a main source of genomic instability in cells of higher eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of ABL1 did not affect cell cycle distribution of BCR-ABL1 cells in response to DNA damage (supplemental Figure 5), but transcriptional microarray analysis revealed that the presence of ABL1 in BCR-ABL1 cells is associated with expression of numerous genes whose products regulate DNA damage response and mitotic spindle assembly checkpoint ( Figure 6G-H Figure 6). 41 Genes involved in kinetochore/spindle/centrosome regulation (Pcid, Csnk2a2, Zwint, Plk2, Nek1) and sister chromatid segregation (Smc1a) are downregulated in BCR-ABL1 Abl1 2/2 cells compared with BCR-ABL1 Abl1 1/1 cells, which may be responsible for abundant aneuploidy in the former cells.…”
mentioning
confidence: 99%